Analisis Penggunaan Sistem Pembayaran QRIS terhadap Perkembangan Bisnis UMKM melalui Kepuasan Nasabah sebagai Variabel Intervening (Studi Kasus Bank Syariah Indonesia (BSI) Kc Sibolga) - Marbun, Astri Novia; Nasution, Yenni Samri Juliati; Harahap, Ikhsan (Lembaga Yasin AlSys, 2023)
This study aims to examine the influence analysis of the use of the Indonesian Standard Quick Response Payment System (QRIS) on MSME business development through Customer Satisfaction as an Intervening Variable (BSI) at KC Sibolga. This research uses quantitative methods. QRIS Payment Respondents at BSI KC Sibolga 50 Merchants using nonprobability sampling. This study used Path Analysis data processing techniques assisted by the IBS SPSS Statistical 25.0 Application. The results of this study indicate that overall for each partial test it says the value α <0.05 in the path analysis test also says there is a direct and indirect effect on each variable that is linked through variable Y and also simultaneously shows that there is a variable that influences the use of QRIS and Customer Satisfaction influences the MSME Business Development. Based on the calculated f value of 9.275 with a significant value of 0.001 <0.05.